A multi-objective decision-making model for renewable energy planning: The case of Turkey - KILIÇ, HÜSEYİN SELÇUK (My University, 2022)
The rapid increase in the world population along with the rising trend of global economic growth triggers serious problems related to energy consumption. In this regard, a comprehensive analysis of the current and potential energy situation in the light of demographic trends, main economic indicators, technical conditions, social and environmental concerns has become a significant issue for developing well-planned global and regional energy strategies. In this study, a multi-objective decision-making model is constructed for renewable energy planning to determine the most appropriate resource diversity for Turkey by focusing on five renewable energy sources, namely solar, wind, geothermal, hydroelectric, and biomass. There are four objective functions presented in the proposed multi-objective model including maximization of the technical score of regions, maximization of the job creation, maximization of the environmental score, and minimization of the cost. As a solution methodology, a two-phase fuzzy goal programming approach is performed. The proposed model is solved using LINGO software as a comprehensive solver for model optimization. The appropriateness of the proposed method is analyzed by comparing it with other multi-objective methods. Results reveal that the majority of the energy demand should be met via solar and hydroelectric energies for the satisfaction of the indicated objectives. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Genel Mühendislik; Genel Enerji; Mühendislik (çeşitli); Yakıt Teknolojisi; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; General Engineering; General Energy; Engineering (miscellaneous); Fuel Technology; Energy (miscellaneous); Physical Sciences; Energy planning; Renewable energy; Multi-objective decision-making; Two-phase fuzzy goal programming; Lexicographic method; Goal programming; WAREHOUSE LOCATION SELECTION; ANALYTIC HIERARCHY PROCESS; GOAL PROGRAMMING-MODEL; ELECTRICITY-GENERATION; FUZZY AHP; MULTICRITERIA APPROACH; MULTIPLE CRITERIA; 2-PHASE APPROACH; REGIONAL LEVEL; OPTIMIZATION